Overview of Discharge Plan Strategies in Rural and Remote Areas: A Narrative Literature Review - Wahyu Wiryawan; Pratama Nurmalik Adhuri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Discharge planning is a systematic process that includes assessment, preparation, and coordination and involves various disciplines to provide optimal service. In Indonesia, there are 62 underdeveloped areas that have limitations in health services. Discharge planning in remote areas requires adaptation to be accepted in the community. This review aims to find an effective patient discharge strategy to be implemented in rural areas. Telepharmaceuticals and telerobots act as discharge planning interventions in remote areas. Remote monitoring, such as a pharmacological intervention in late life (PILL) program that focuses on monitoring the treatment of patients with polypharmacy. Interprofessional education and collaborative practice (IPECP) is suitable to be carried out in remote areas where limited facilities stimulate health workers to collaborate. Patient activation measure (PAM) to assess the ability and engagement of patients in maintaining their health. In addition, interventions were found in the form of making patient-centered guidelines in the form of ROADMAP (rural options at discharge - model of active planning).